Science and scientists from children’s point of view: comparison and gender outlooks among 2011 and 2021 primary school student drawings - D’Addezio, Giuliana; Besker, Neva (Frontiers in Education, 2024)
This article explores the evolving perceptions of science and scientists from the unique perspective of Italian primary school children by comparing students' drawings from two distinct periods, 2011 and 2021. A notable research gap exists in understanding how the perceptions of science and scientists among primary school children have evolved over time and if it is different for gender and grade level. The methodology involves a qualitative analysis of drawings examining the presence, the number and gender of depicted scientists, stereotypes, scientific topics, inventions, tools, location, and accompanying speech bubbles. The statistical analysis emphasizes the differences between how girls and boys represent science and scientists. From the data, a generally positive picture of the work of scientists emerges, as well as a great level of confidence in the potential of science. Notably, while the prevailing image of a scientist is still predominantly male, the 2021 dataset demonstrates a significant increase in depictions of female scientists, primarily drawn by girls, signaling an increased sense of belonging and potential for girls to pursue careers in science. Environmental and health-related scientific themes have gained prominence, accompanied by an increase in inventive ideas. The data highlights the children's awareness of pressing global issues, such as climate change and healthcare, caused by Covid emergency. Furthermore, the results contribute to evaluate how science showed itself over ten years, if it has led to an effective shared science and a less stereotyped image, also encouraging gender equality.